2018
DOI: 10.1038/s41598-018-26221-x
|View full text |Cite
|
Sign up to set email alerts
|

Allergy immunotherapy restores airway epithelial barrier dysfunction through suppressing IL-25 -induced endoplasmic reticulum stress in asthma

Abstract: Constant exposure to allergen triggers destructive type 2 cell-mediated inflammation. The effect of allergen specific immunotherapy (SIT) in maintaining airway epithelial barrier function in asthma remains unknown. In the current study, we showed that SIT maintained airway epithelial homeostasis in mice exposed to dermatophagoides farinae (Der f), which induced increased expression of IL-25, endoplasmic reticulum (ER) stress and airway epithelial apoptosis. Meanwhile, SIT treatment ameliorated airway inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Recent evidence suggested that the disturbance of the epithelial barrier as a common feature in many allergic inflammatory disorders included food allergy, asthma, and atopic dermatitis 24,25 . And the latest study also found that in the causes of allergic asthma inflammation, the damage of the bronchial epithelial integrity was considered to be the starting point for the development of airway inflammation in asthma 26‐28 . The integrity of the epithelial barrier was dependent on TJs, AJs, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggested that the disturbance of the epithelial barrier as a common feature in many allergic inflammatory disorders included food allergy, asthma, and atopic dermatitis 24,25 . And the latest study also found that in the causes of allergic asthma inflammation, the damage of the bronchial epithelial integrity was considered to be the starting point for the development of airway inflammation in asthma 26‐28 . The integrity of the epithelial barrier was dependent on TJs, AJs, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no studies in humans have demonstrated a reduction of epithelium-derived pro-inflammatory cytokines following AIT. However, a recent study of SCIT in a murine Der f-sensitized model demonstrated a reduced IL-25 secretion and restoration of epithelial integrity by ameliorating said cytokine-related endoplasmic reticulum stress and EC apoptosis [ 99 ]. However, such findings remain to be replicated in human models.…”
Section: Mechanisms Of Allergic Rhinitismentioning
confidence: 99%
“…It has been shown that IL-33 activated ILC2s disrupted airway epithelial barrier through IL-13 mediated inhibition of expression of tight junction proteins [38]. Therefore, it would be possible to ameliorate asthma by improving airway epithelial integrity through inhabiting airway epithelial ER stress and apoptosis [39]. Molecular hydrogen indeed suppressed the activation of caspase 3 and 9 in asthmatic mouse airway tissue and restored the levels of E-cadherin and ZO-1.…”
Section: Discussionmentioning
confidence: 96%